Perspectives of scholars on the origin, spread and consequences of COVID-19 are diverse but not polarized - Prakash Kumar Paudel; Rabin Bastola; Sanford D. Eigenbrode; Amaël Borzée; Santosh Thapa; Dana Rad; Jayaraj Vijaya Kumaran; Suganthi Appalasamy; Mohammad Mosharraf Hossain; Anirban Ash; Raju Adhikari; Roshan Babu Ojha; et al. (Humanities & Social Sciences Communications, 2022)
Abstract The coronavirus disease 2019 (COVID-19) pandemic, caused by severe acute respiratory syndrome coronavirus 2, has devastated every sphere of human society. Governments around the world implemented unprecedented policies designed to slow the spread of the disease and assistance to cope with its impacts. Such policies, however, are short-term and debates have ensued about what broader policies are needed in the post-COVID-19 era to ensure societies are better prepared for future pandemics. Public opinion concerning COVID-19 and the post-COVID-19 era is diverse, and the patterns in opinion are not well documented. Here we synthesized the opinions of 3731 research scholars throughout the world based on a survey. The highest consensus among respondents concerned the need for improving public health infrastructure and delivering economic support, whereas agreement concerning ecological aspects was low. The survey revealed three dimensions of thinking about COVID-19. The first dimension relates to public health and has widespread support. The second dimension relates to science-led policy development focusing on social justice and environmental governance, covering components of both ecology and economy. The third dimension covers the role of nature conservation in reducing the risk of pandemics. Although opinions differed with age, country of citizenship, and level of education, there is strong agreement on the need for global health equity and science-led public policy.